Isolamento e caracterização parcial dos Genes beta-actina e miosina de cadeia pesada do Camarão rosa Farfantepenaeus subtilis - Ribeiro, Eliana Matos (2009)
The penaeid shrimp Farfantepenaeus subtilis is an important native species for fisheries industry in Brazil. Among marine shrimps of commercial importance, penaeids are recognized as a valuable resource for fishery and aquaculture in tropical and subtropical regions. However, data on these species is extremely reduced, especially concerning genetic elements involved in animal muscle growth. Therefore, aiming at identifying shrimp genes directly associated with muscle contraction in this research, beta-actin and myosin heavy chain genes of the pink shrimp F. subtilis were isolated from its muscular abdominal and partially sequenced. Shrimps collected from Pacoti estuary, Ceará, were first identified through taxonomy and, then, through DNA amplification followed by sequencing of Cytochrome Oxidase subunit I (COI) and 16S. From fresh shrimp tissues, total RNA was extracted and complementary cDNA was obtained. Based on specific primers designed after sequence alignments performed against sequences at GenBank/NCBI, genes were amplified from RT-PCR (reverse transcriptase - polimerase chain reaction) and sequenced. A 760bp partial F. subtilis beta-actin cDNA fragment was obtained, while the partial F. subtilis myosin heavy chain cDNA was 570bp long. Sequence analyses using the Basic Local Alignment Search Tool (BLAST) program indicated that F. subtilis beta-actin gene product is very similar to betaactin of other species of shrimps, while the myosin heavy chain protein is highly homologous to crustacean myosins heavy chain, confirming the identity of the isolated gene sequences. Alignment of these gene sequences with other sequences in GenBank showed high similarity with Penaeus monodon (93%) and Farfantepenaeus paulensis (88%). Results have showed the feasibility of partial gene identification as a means to identify genes of strategic interest. These data would help further attempts to elucidate the complete isolation of these genes, as well as the detection of other important genes, especially from shrimp species occurring at the Brazilian coast. Genes analyses involved with muscle growth might provide important genetic information on native species that are overexploited and may be viable for the shrimp cultivation. In addition, these data might also benefit the scientific community, improving a range of research areas such as physiology, phylogeny and evolution of penaeids